2013
DOI: 10.1123/ijsc.6.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Image-Restoration Strategies: An Integrated Case Study of Three Athlete Sex Scandals in Sports News

Abstract: A limited number of studies have examined the effectiveness of apology techniques in image restoration of athletes involved in sex scandals. This case study used Benoit’s (1995) image-restoration strategies to examine the apology techniques 3 athletes used to negotiate their sex scandals and attempted to encourage further discussion of these techniques. Three athletes’ sex scandals were comparatively analyzed, including those of golfer Tiger Woods, National Football League quarterback Ben Roethlisberger, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…It is observed that consumers display low involvement behaviour with scandalized athletes (Sato, Ko, Park, & Tao, 2015). For instance, three top athletes -golfer Tiger Woods, National Football League quarterback Ben Roethlisberger, and the National Basketball Association's Kobe Bryant -were caught in and apologized for sex scandals, thus harming their huge fan following; they also faced media rage and loss of endorsements (Meng & Pan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that consumers display low involvement behaviour with scandalized athletes (Sato, Ko, Park, & Tao, 2015). For instance, three top athletes -golfer Tiger Woods, National Football League quarterback Ben Roethlisberger, and the National Basketball Association's Kobe Bryant -were caught in and apologized for sex scandals, thus harming their huge fan following; they also faced media rage and loss of endorsements (Meng & Pan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…B. Blaney, Lippert, & Smith, 2013;Brown, Dickhaus, & Long, 2012;Liu, 2007;Meng & Pan, 2013;Sheldon & Sallot, 2008…”
Section: Moral Rationalizationmentioning
confidence: 99%
“…The selection process of an athlete endorsers requires careful strategic consideration with an aim to find an endorser that is most congruent in terms of their image with the brand. Companies aim to select the athlete endorser that fits with the brand identity and image and that can transfer positive image, associations and meanings to the brand (98). As athletes are considered as role models who should have clean social images, there should be no surprise image is regarded as one of the criteria that is considered by the sponsors (99).…”
Section: Athlete Selection the Key Criteria'smentioning
confidence: 99%